2020
DOI: 10.1108/whatt-05-2020-0022
|View full text |Cite
|
Sign up to set email alerts
|

Responsible tourism education of younger consumers: the role of mini-clubs in mountain resorts

Abstract: Purpose The purpose of this viewpoint paper is to discuss whether children can play a role in the sustainability of the tourism industry as a whole. Design/methodology/approach The paper is based on a literature review of key terms: sustainable tourism; mountain tourism; children; and empowerment. Findings Children could potentially play a role in the sustainability of tourism if they are empowered to do so. mini-clubs in mountain resorts could, for instance, contribute to their social empowerment using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The themes "social" and "play" are particularly important elements in the research on children's humour, as indicated by the analysis of the various articles in this study, as these two themes can be extended to tourism contexts. Cultural and environmental tourism sites offer educational and social contexts where children can benefit from play activities (Seraphin, 2020) and interact with different individuals, particularly tour guides, facilitators, and peers. Children recognise social interactions and making new friends as significant motivations for their holidays (Larsen & Jenssen, 2004).…”
Section: Tourism Sites As a Social Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…The themes "social" and "play" are particularly important elements in the research on children's humour, as indicated by the analysis of the various articles in this study, as these two themes can be extended to tourism contexts. Cultural and environmental tourism sites offer educational and social contexts where children can benefit from play activities (Seraphin, 2020) and interact with different individuals, particularly tour guides, facilitators, and peers. Children recognise social interactions and making new friends as significant motivations for their holidays (Larsen & Jenssen, 2004).…”
Section: Tourism Sites As a Social Contextmentioning
confidence: 99%
“…Hammershøj (2021) describes play as "humour in action" of a linguistic nature. This aspect should not be overlooked, as it plays a crucial role in offering children engaging and enjoyable activities that are instrumental in educating them about sustainability issues (Seraphin, 2020). Language play as a linguistic activity offers fresh perspectives for future tourism studies.…”
Section: The Importance Of Playmentioning
confidence: 99%